1986
DOI: 10.3168/jds.s0022-0302(86)80366-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cell Counts in Goat Milk and Their Correlations with Somatic Cell Counts, Percent Fat, and Protein

Abstract: Representative milk samples at morning and afternoon milking were collected periodically for 5 mo from 32 does in a Prairie View A&M University milking herd to test the concentrations of total bacterial, coliform, and staphylococcus counts and to determine the correlations among the bacterial cell counts, somatic cell counts, percent fat, and percent protein. Bacterial cell counts were assayed by microbiogical methods using different nutrient media for the three cell types. Somatic cell counts were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 8 publications
2
25
1
7
Order By: Relevance
“…Alguns autores (Contreras et al 1996, Silva 1997, Park & Humphrey 1986, Andrade et al 2001, Fernandes 2002 encontraram valores médios maiores que os obtidos neste estudo. Sabe-se que o número de células somáticas presentes no leite é influenciado por diversos fatores não-infecciosos, tais como número de lactações, raça, ambiente de criação e tipo de ordenha empregado, fatos que poderiam justificar as diferenças nas contagens encontradas em relação aos trabalhos acima citados.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Alguns autores (Contreras et al 1996, Silva 1997, Park & Humphrey 1986, Andrade et al 2001, Fernandes 2002 encontraram valores médios maiores que os obtidos neste estudo. Sabe-se que o número de células somáticas presentes no leite é influenciado por diversos fatores não-infecciosos, tais como número de lactações, raça, ambiente de criação e tipo de ordenha empregado, fatos que poderiam justificar as diferenças nas contagens encontradas em relação aos trabalhos acima citados.…”
Section: Discussionunclassified
“…Sabe-se que o valor da contagem de células somáticas aumenta com o avançar da lactação, fato já relatado por diversos autores (Droke et al 1993, Gonzalo 1995, Gomes 2003. Alguns autores (Park & Humphrey 1986, Droke et al 1993, Gonzalo 1995 verificaram maiores níveis celulares nas primeiras semanas pós-parto, os quais diminuíram durante o período de máxima produção de leite, voltando a aumentar até o final da lactação, resultados também observados neste trabalho.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…These results show that sheep tissues remain alive for longer time followed by bovine and goat. Perhaps it may be due to less amount of fat in goat tissues as compared to bovine and sheep (Park & Humphrey, 1986). …”
Section: Resultsmentioning
confidence: 99%
“…In other studies, however, higher fat concentration was found in infected glands than in uninfected ones [20] or related to high levels of SCC [6]. Positive [18,20,21]; negative [22,23] or no relationship [9] was also described between protein content and SCC or intramammary infection. The variation of milk contents could be also associated with a dilution or concentration effect in variable milk volumes similarly to SCC, as suggested, for example, Fuertes et al [21].…”
Section: Introductionmentioning
confidence: 95%